2013
DOI: 10.3402/tellusb.v65i0.21120
|View full text |Cite
|
Sign up to set email alerts
|

O<sub>2</sub>:CO<sub>2</sub> exchange ratios observed in a cool temperate deciduous forest ecosystem of central Japan

Abstract: Detailed observations of O2:CO2 exchange ratios were conducted in a cool temperate deciduous forest located in central Japan. The exchange ratios of soil respiration and net assimilation were found to be 1.11±0.01 and 1.02±0.03 from soil chamber and branch bag measurements, respectively. Continuous measurements of the atmospheric O2/N2 ratio and the CO2 concentration, made inside the canopy during a summer season, indicated that the average exchange ratio was lower in the daytime (0.87±0.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
41
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(65 citation statements)
references
References 38 publications
6
41
0
Order By: Relevance
“…Other soils incubated in that study in an open system with no CO 2 buildup gave values of 0.83-0.95 and of 0.84 for an in situ soil-chamber experiment. Seibt et al (2004) reported values in a forest soil chamber which correspond to the respiratory quotient (RQ) of 1.5 (and to 1.06 after removing one data point which was considered to be an outlier): this is higher than the 0.90 value reported recently for a soil chamber in a forest in Japan (Ishidoya et al, 2013). An average value of 1.0 for soil profiles were found in the Amazonian tropical forest in Peru (Angert et al, 2012).…”
Section: Introductionmentioning
confidence: 48%
“…Other soils incubated in that study in an open system with no CO 2 buildup gave values of 0.83-0.95 and of 0.84 for an in situ soil-chamber experiment. Seibt et al (2004) reported values in a forest soil chamber which correspond to the respiratory quotient (RQ) of 1.5 (and to 1.06 after removing one data point which was considered to be an outlier): this is higher than the 0.90 value reported recently for a soil chamber in a forest in Japan (Ishidoya et al, 2013). An average value of 1.0 for soil profiles were found in the Amazonian tropical forest in Peru (Angert et al, 2012).…”
Section: Introductionmentioning
confidence: 48%
“…Therefore, in this study, we present the average diurnal cycle of ER F and its daily mean values obtained at TKY for the period May 24-August 28, 2013, using an aerodynamic method (Yamamoto et al 1999). We also decomposed the measured NEP over the same period, obtained using an eddy covariance method (Saigusa et al 2005), into GPP and RE using the average daily mean ER F observed in this study in combination with the assumed ER A and ER R values at TKY based on the results reported by Ishidoya et al (2013). The separate GPP and RE were then compared with those estimated from an empirical function of air temperature (Saigusa et al 2005) and with soil CO 2 efflux measured using an open-flow soil chamber method (Mo et al 2005a, b).…”
Section: Introductionmentioning
confidence: 95%
“…Recently, Ishidoya et al (2013) observed O 2 :CO 2 exchange ratios (ER = À DO 2 DCO 2 À1 molar exchange ratio) of soil respiration, net assimilation (GPP À leaf respiration), and the forest canopy air at the Takayama cool temperate deciduous broadleaf forest site in central Japan (36°09¢N, 137°25¢E, 1420 m a.s.l. ; designated TKY in the Asia Flux site code database).…”
Section: Introductionmentioning
confidence: 99%
“…Measurements of atmospheric δ(O 2 /N 2 ) and CO 2 mole fraction have also been made using continuous in situ monitors (e.g. Lueker et al, 2003;Lueker, 2004;Yamagishi et al, 2008;van der Laan-Luijkx et al, 2010;Goto et al, 2013a;Ishidoya et al, 2013), revealing small and short-term fluctuations in atmospheric δ(O 2 /N 2 ) and APO, thereby providing new insight into the carbon cycle. Lueker et al (2003) and Lueker (2004) observed low values of APO at the Trinidad Head coastal site in California (41.05°N, 124.15°E), lasting for several days or weeks.…”
Section: Observation Site and Measurement Systemmentioning
confidence: 99%